Design of BIPA learning based on short story “Basa-Basi” for understanding the phenomenon of chit-chat in Indonesian society - Rudi Ekasiswanto; Kurniawati , Wira; Warouw , Nicolas (BAHASTRA, 2024)
Chit-chat is a socio-cultural phenomenon ethnographically embedded in Indonesian society's culture, also discursively presented in literary works, namely the short story "Basa-Basi" by Yohanes Prananto. This research aims to outline a BIPA learning design based on literary works to understand the phenomenon of chit-chat. Methodologically, this research uses the literature study, development, and retrospection. This research finds that literary works can be applied to listening-reading, speaking, writing, and Indonesian insight skills. The short story “Basa-Basi” is presented as reading material for students. It is classified as a simple literary work because the degree of structural complexity is not that high. So, it is considered appropriate for advanced students 1. In speaking skills, students are asked to express their ideas about the substance of the short story in general and specifically about the chit-chat. Through this short story, students receive Indonesian insights and cross-cultural comparisons. After that, students are asked to compare it with equivalent phenomena in their countries of origin. The results of this comparison are applied to narrative writing skills of 300-500 words. The procedure is derived from a pragmatic approach for BIPA teaching, which situates language learning within its context. Through literature-based BIPA learning, with the formulated approach, design, and procedures, this research underlines that the use of literary works enables learners to not only learn the language but also understand the socio-cultural phenomena within the community of the language speakers.